2002
DOI: 10.1136/jcp.55.7.499
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the sensitivity of death certificates in 440 hospital deaths: a comparison with necropsy findings

Abstract: There is a substantial discrepancy between the diagnosis given on death certificates compared with that at hospital necropsy. This paper discusses the importance of clinicopathological concordance and emphasises the importance of the necropsy in death certification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
88
1
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(96 citation statements)
references
References 14 publications
6
88
1
1
Order By: Relevance
“…Any bias was most likely nondifferential because completeness of the National Death Index is well validated (38). The accuracy of cause of death on death certificates remains equivocal (30,39). We reached similar conclusions when using all-cause mortality (the primary end point of interest) or breast cancer -specific mortality.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Any bias was most likely nondifferential because completeness of the National Death Index is well validated (38). The accuracy of cause of death on death certificates remains equivocal (30,39). We reached similar conclusions when using all-cause mortality (the primary end point of interest) or breast cancer -specific mortality.…”
Section: Discussionsupporting
confidence: 60%
“…Because the quality of cause of death information on death certificates has been questioned in at least one study (30), all-cause mortality was the main end point, and patients alive at the end of follow-up were censored. Analyses of breast cancer -specific mortality were also conducted, and participants who died of causes other than breast cancer were censored.…”
Section: Methodsmentioning
confidence: 99%
“…The validity of the cause of death registrations can be questioned because previous studies have found that subsequent autopsies revealed an incorrect registration of the cause of death on a relatively high proportion of death certificates [31][32][33][34]. This is, however, a problem for all studies relying on death certificates to determine the cause of death.…”
Section: Discussionmentioning
confidence: 74%
“…Difficulties with diagnosis: Many of the studies that have reported excess ovarian cancer following asbestos exposure have examined mortality from ovarian cancer and used the cause of death as listed on the death certificate to identify the cause of death. The accuracy of death certificates has been questioned repeatedly (7,8), particularly in relation to asbestos-related diseases (9). Pleural mesothelioma has a long history of being misreported on death certificates most often being labeled as lung or pleural cancer (3,9,10).…”
Section: Introductionmentioning
confidence: 99%